2015
DOI: 10.15408/ijies.v7i1.1359
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Variable and Its Influence on Performance of Indonesian Islamic Banking

Abstract: Macroeconomic Variables and Its Influence on Performance of Indonesian Islamic Banking. The purpose of this research is to analyze the macroeconomics variables that affect to the performance of Islamic banks in Indonesia. Methods used in this research is the Vector Auto regressive (VAR) / Vector Error correction model (VECM) to see the effect of the shock and the long-term effect on the performance of Islamic Banking. The results show that based on the analysis of IRF, the performance of Islamic banking having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…They found that the Indonesian Islamic stock market was very much influenced by the international Islamic stock markets. Using similar technique of analysis, Pratama (2015) explored the impacts of macroeconomic variables to the performance of Islamic banks in Indonesia for the period 2007-2012. He found that the performance of Islamic banks having short-term shocks to the innovations of macroeconomic variables, but it become stable in the long-run.…”
Section: Gordon Growth Model Had Simplified the Valuation Of Stock Asmentioning
confidence: 99%
“…They found that the Indonesian Islamic stock market was very much influenced by the international Islamic stock markets. Using similar technique of analysis, Pratama (2015) explored the impacts of macroeconomic variables to the performance of Islamic banks in Indonesia for the period 2007-2012. He found that the performance of Islamic banks having short-term shocks to the innovations of macroeconomic variables, but it become stable in the long-run.…”
Section: Gordon Growth Model Had Simplified the Valuation Of Stock Asmentioning
confidence: 99%
“…There are also external factors that affect the company's financial performance, namely macroeconomic variables (Pratama, 2015). It is of course also important to know the impact on Islamic banking activities because external factors cannot be controlled by banks, so what banks must do is have a way to anticipate the condition of macroeconomic variables so as not to hurt banks.…”
Section: Introductionmentioning
confidence: 99%